Soroprevalência de leptospirose em cavalos com transtornos reprodutivos - Farias, D. K.; Dick, G.; Cunha, A. P.; Nascimento, J.; Coelho, M. E.; Thomé, J.; Reck, C.; Saito, M. E.; Menin, A. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2019)
Leptospirosis is an important zoonotic-disease of global importance and worldwide distribution that cause reproductive failure (abortions/stillbirths) and uveitis in horses. The horses are susceptible to different f Leptospira spp. serovars, and the prevalence may vary according to region, seasonality, and risk factors.